Biomass char particle surface area and porosity dynamics during gasification. (15th March 2020) - Wu, Ruochen; Beutler, Jacob; Price, Cameron; Baxter, Larry L.
Highlights: Biomass char surface areas monotonically increase during gasification. Biomass chars maintain organic structure throughout pyrolysis and char oxidation. Char micropores do not change during conversion and therefore probably are not reactive. Biomass vascular structure affects reactivity but is not measured by traditional techniques. Abstract: Experimental measurements of industrially relevant biomass char particles (12.5 mm and smaller) undergoing kinetics-limited gasification reactions with CO2 and H2 O reveal how porosity and surface area change with char conversion. Reactant concentrations range from 0 to 90% CO2 and 0–50% H2 O, including mixtures of both reactants. Reactor temperatures range from 1150 °C to 1350 °C. Particle types include wood (poplar), an herbaceous energy crop (switch grass), and an agricultural residue (corn stover). The data include measurements of particle size, shape, and mass as essentially continuous functions of time combined with discrete measurements of surface area and porosity and provide a robust data set for comparison. Theoretical predictions of porosity from standard models do not adequately describe the experimental trends. Total surface area increases slightly with conversion, with most of the increase in the largest pores but most of the surface area in the small pores. Porosity also increases uniformly with conversion·H2 O, CO2 and blended gasification environments produce qualitatively similar surface area and porosity data over wide ranges of reactant concentrations when plotted against conversion. Char particle diameters slightly decrease during these kinetically controlled reactions, in part because of sintering and in part because the reaction is endothermic and creates a decreasing particle temperature gradient toward the particle center. Therefore, the particle center reacts more slowly than the comparatively warmer char surface. An abrupt change in char diameter occurs at conversions greater than 99.5% associated with residual ash sintering. SEM images qualitatively confirm the quantitative measurements and show that the biomass microstructure remains easily recognizable through essentially the entire conversion process. The primary conclusions indicate that (1) the vascular structure appears to have a major role in particle reactivity, is preserved during essentially the entire char conversion history, and is not captured by BET or similar analysis techniques, (2) the pore models developed for coal and other chars do not describe and cannot be adjusted to reasonably describe the development of surface area observed in these experiments, and (3) the great majority of the surface area is in the nanopores which do not change at all during conversion and appear to have no influence on char reactivity. The larger pores, and especially the vascular structure, primarily contribute to reactive surface area.